The politics of imperial memory in France, 1850-1900 - Carroll, Christina B., 1984- (Cornell University Press, 2022)
"The Politics of Imperial Memory in France examines the shifting role played by the memory of continental-and especially Napoleonic-imperial models in the contested construction of France's expansive "new" colonial empire during the second half of the nineteenth century"--